Titin isoform size is not correlated with thin filament length in rat skeletal muscle - Greaser, Marion L.; Pleitner, Jonathan M. (Frontiers in Physiology, 2014)
The mechanisms controlling thin filament length (TFL) in muscle remain controversial. It was recently reported that TFL was related to titin size, and that the latter might be involved in TFL determination. Titin plays several crucial roles in the sarcomere, but its function as it pertains to the thin filament has not been explored. We tested this relationship using several muscles from wild type rats and from a mutant rat model (Greaser et al., 2008) which results in increased titin size. Myofibrils were isolated from skeletal muscles [extensor digitorum longus (EDL), external oblique (EO), gastrocnemius (GAS), longissimus dorsi (LD), psoas major (PM), and tibialis anterior(TA)] using both adult wild type (WT) and homozygous mutant (HM) rats (n = 6 each). Phalloidin and antibodies against tropomodulin-4 (Tmod-4) and nebulin's N-terminus were used to determine TFL. The WT rats studied express skeletal muscle titin sizes ranging from 3.2 to 3.7 MDa, while the HM rats express a giant titin isoform sized at 3.8 MDa. No differences in phalloidin based TFL, nebulin distance, or Tmod distance were observed across genotypes. However, the HM rats demonstrated a significantly increased (p < 0.01) rest sarcomere length relative to the WT phenotype. It appears that the increased titin size, predominantly observed in HM rats' middle Ig domain, allows for increased extensibility. The data indicates that, although titin performs many sarcomeric functions, its correlation with TFL and structure could not be demonstrated in the rat.